Integrated Gate Commutated Thyristor: From Trench to Planar - Vemulapati, Umamaheswara; Stiasny, Thomas; Wikstrom, Tobias; Lophitis, Neophytos; Udrea, Florin (My University, 2020)
The planar Integrated Gate Commutated Thyristor (IGCT) concept is proposed to simplify the fabrication process of the device and improve the ruggedness as well as electrothermal performance of the device. The planar IGCT concept has been verified experimentally with 4.5kV devices fabricated on 4-inch Si wafers. Afterwards, the electrical characteristics of the planar IGCT were compared with that of the conventional (with trench or mesa gate) IGCT. Both the planar and the conventional IGCTs are fabricated with corrugated p-base referred to as High Power Technology (HPT) design. In addition, mixed-mode TCAD device simulations have been performed to verify the turn-off failure mechanism and to analyze the electro-thermal performance of the planar IGCT in reference to that of the conventional IGCT.
Keywords: discrete power semiconductor; high power semiconductor switch; IGCT; planar-gate; Thyristor; trench-gate